Teacher and Student Perceptions Towards The Use of Technology-Based Learning Media in High School - Renaldi, Reno (Lembaga Riset dan Inovasi Almatani, 2025)
The use of technology-based learning media in Senior High Schools (SMA) is an important innovation in modern education. This study aims to describe teachers' and students' perceptions of the use of technology-based learning media, analyze the challenges and opportunities for its implementation, and identify supporting and inhibiting factors in the process of technology integration in the school environment. The research method used is descriptive qualitative, with data collection techniques including interviews, observation, and documentation. The results show that both teachers and students have positive perceptions of the use of technology-based media because they are considered capable of increasing motivation, effectiveness, interactivity, and learning independence. However, limited facilities, technological competence, and training support remain major obstacles. This study emphasizes the importance of collaboration between schools, teachers, students, and the government in optimizing the use of technology-based learning media to improve the quality of education in the digital era.